Exploring determinants of county suburban vegetable planting via the fsQCA-NCA approach - Wei, Wei; Tang, Huacang; Ma, Hengyun (Frontiers in Sustainable Food Systems, 2024)
Taking 26 county suburban areas of significant vegetable growers in Henan Province as a case study, this paper constructs a theoretical framework for market demand, market supply, and market environment on the basis of the conditions constraining the scaling up of vegetable production in county suburbs. Six indicators are selected to measure the vegetable planting scale in different counties/districts. Using fuzzy-set qualitative comparative analysis (fsQCA) and necessary condition analysis (NCA) methods, ten configurations are analyzed. The results show that the main paths for achieving large-scale vegetable production in county suburban areas rely primarily on market demand, followed by market environment. On the basis of these findings, to improve vegetable production levels in Henan Province, efforts should focus on aligning with the willingness of vegetable growers, enhancing both the soft and hard environments for vegetable production, and nurturing and introducing leading vegetable enterprises to build the vegetable industry chain. These measures will gradually promote the realization of large-scale vegetable production in county suburban areas.